Analysis of the possibility of accounting for the antenna reflection coefficient in displacement measurements by probe methods - Pylypenko, O.V.; Doronin, A.V.; Gorev, N.B.; Kodzhespirova, I.F. (Технічна механіка, 2019)
Цель данной работы заключается в выборе зондового метода измерения перемещения, который может быть модифицирован с тем, чтобы учесть коэффициент отражения рупорной антенны, пренебрежение которым может оказаться недопустимым при достаточно большом расстоянии между антенной и контролируемым объектом. Мета цієї роботи полягає у виборі зондового методу вимірювання переміщення, який може бути модифікований з тим, щоб урахувати коефіцієнт відбиття рупорної антени, нехтування яким може бути неприпустимим при достатньо великій відстані міх антеною й контрольованим об’єктом. The aim of this work is to choose a probe method for displacement measurement that could be modified to account for the horn antenna reflection coefficient, which can hardly be neglected if the target–antenna distance is large enough.